The Place of Home-Based Enterprises in the Household Economies of the Low-Income Families in Kumasi: Analysis of Contributions and Linkages (Journal of Science and Technology, 2016)
The study examined the place of home-based enterprises (HBEs) in the household economies of low-income families in Kumasi. Ii adopted a case study approach that combined quantitative and qualitative methods with Ayigya and Asawase communities as case studies. Evidence from the study amply established that HBEs are not merely marginal economic activities in poor neighbourhoods, but rather, they are important sources of income and employment. It was also revealed that a complex but well-defined relationship exist between the household members and the businesses In terms of ownership and management of the HBEs. Finally. the operations of the HBEs were found to be inseparably linked to and functionally integrated into the family lives of the households in several ways. The implications of these findings for policy have been examined in the paper.